2018
DOI: 10.3390/ma11112090
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Treated TiO2 for Enhanced Performance in Aqueous Al-Ion Batteries

Abstract: The potential for low cost, environmentally friendly and high rate energy storage has led to the study of anatase-TiO2 as an electrode material in aqueous Al3+ electrolytes. This paper describes the improved performance from an electrochemically treated composite TiO2 electrode for use in aqueous Al-ion batteries. After application of the cathodic electrochemical treatment in 1 mol/dm3 KOH, Mott–Schottky analysis showed the treated electrode as having an increased electron density and an altered open circuit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…So, the valence band potential ( E VB ) is 1.68 V. It is measured that the E fb of pure TiO 2 is −0.40 V (vs Ag/AgCl), which is shown in Figure S11. This result strongly agreed with that previously reported by Kim and Holland et al. , Hence, the E CB of TiO 2 is −0.40 V and E VB is 2.60 V because the band gap of TiO 2 is 3.00 eV (Figure b). The n–n junction of both CeO 2 and TiO 2 is represented in Scheme .…”
Section: Resultssupporting
confidence: 93%
“…So, the valence band potential ( E VB ) is 1.68 V. It is measured that the E fb of pure TiO 2 is −0.40 V (vs Ag/AgCl), which is shown in Figure S11. This result strongly agreed with that previously reported by Kim and Holland et al. , Hence, the E CB of TiO 2 is −0.40 V and E VB is 2.60 V because the band gap of TiO 2 is 3.00 eV (Figure b). The n–n junction of both CeO 2 and TiO 2 is represented in Scheme .…”
Section: Resultssupporting
confidence: 93%
“…It is demonstrated that the inferior diffusion of Al 3+ ions within TiO 2 is due to the poor electronic conductivity of TiO 2 , which can be improved by the introduction of a small fraction of graphene . Furthermore, various synthesis methods have been studied, such as incorporation of CNT and electrochemical treatment. , For positive electrode materials used in aqueous RABs, metal oxide and carbon electrodes are mainly screened on the basis of the reported literature. Lahan et al demonstrated an effective approach for improving conductivity by adding graphene additive .…”
Section: Classification Of Positive Electrode Materials For Nonaqueou...mentioning
confidence: 99%
“…147 Furthermore, various synthesis methods have been studied, such as incorporation of CNT and electrochemical treatment. 148,149 For positive electrode materials used in aqueous RABs, metal oxide and carbon electrodes are mainly screened on the basis of the reported literature. Lahan et al demonstrated an effective approach for improving conductivity by adding graphene additive.…”
Section: Classification Of Positive Electrode Materials For Nonaqueou...mentioning
confidence: 99%
“…The most researched component for aluminum-ion batteries is the cathode. The research can be divided into six groups based on the type of material used for the cathode: metal oxides [127][128][129][130][131][132], metal sulfides [133][134][135][136][137], carbon [138,139], metal selenides [14,140] metal phosphides [141,142] and metal phosphite [143]. Here we highlight those works that focus on the function of the material.…”
Section: Aluminum-ion Batteriesmentioning
confidence: 99%